Uterine adenomatoid tumor: a clinicopathologic study of 102 cases - Chen, Hong-Fang (Int J Clin Exp Pathol, 2017)
Objective: Uterine adenomatoid tumors (UATs) are tubercle without significant clinical features. The study aims to summarize the clinicopathological characteristics of UATs to improve diagnostic accuracy. Methods: Between January 2014 and December 2015, 4326 uterine specimens were collected from patients who received hysterectomy or myomectomy, of which 102 cases were pathologically confirmed as UATs. The clinical features, pathological parameters and immunohistochemical staining were analyzed. Results: One hundred and two UATs were identified by gross and microscopic examination, which accounts for 2.4% of all the uterine tumors. UATs were usually located in the uterus myometrium, near the serosa or cornua. Most of them were solitary, without an enveloping membrane or clear demarcation. Microscopically, typical features were glandular structures and cavities with various sizes and shapes found within the hyperplastic smooth muscle tissues. Immunohistochemical staining showed that all tumors were positive for HBME-1 and CK (pan). Most of them were positive for CR (89.6%) and D2-40 (92.4%), negative for CD31 and CEA, while cast-off cells in glandular cavities and lymphocytes were positive for LCA. Conclusion: Adenomatoid tumors are not very rare in the uterus. The diagnosis of UATs can be improved by carefully gross and microscopic examination. Immnohistachemical staining is helpful for diagnosis and differential diagnosis of UATs.